2015
DOI: 10.1158/1078-0432.ccr-15-1522
|View full text |Cite|
|
Sign up to set email alerts
|

SAR405838: A Novel and Potent Inhibitor of the MDM2:p53 Axis for the Treatment of Dedifferentiated Liposarcoma

Abstract: Purpose Dedifferentiated liposarcoma (DDLPS) is an aggressive malignancy that can recur locally or disseminate even after multidisciplinary care. Genetically amplified and expressed MDM2, often referred to as a “hallmark” of DDLPS, mostly sustains a wild-type p53 genotype, substantiating the p53-MDM2 axis as a potential therapeutic target for DDLPS. Here we report on the preclinical effects of SAR405838, a novel and highly selective MDM2 small-molecule inhibitor, in both in vitro and in vivo DDLPS models. Ex… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
79
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 88 publications
(81 citation statements)
references
References 30 publications
1
79
0
Order By: Relevance
“…MDM2 and CDK4 were already familiar as important factors in the pathological diagnosis of liposarcoma, but as MDM2-or CDK4-targeted drugs were investigated, their efficacies against STS (especially liposarcomas) were also evaluated. The investigation of MDM2 inhibitors has been limited to preclinical and early-phase trials [68,69], but there are some phase 2 results for CDK4 inhibitors; liposarcomas showed modest responses to them [70,71]. However, the response rates were not high enough to obtain approval for a single-arm phase 2 trial, and further randomized clinical trials are necessary to confirm the clinical efficacies of CDK4 inhibitors.…”
Section: Investigating Molecular Targeted Therapies For Sts Patientsmentioning
confidence: 99%
“…MDM2 and CDK4 were already familiar as important factors in the pathological diagnosis of liposarcoma, but as MDM2-or CDK4-targeted drugs were investigated, their efficacies against STS (especially liposarcomas) were also evaluated. The investigation of MDM2 inhibitors has been limited to preclinical and early-phase trials [68,69], but there are some phase 2 results for CDK4 inhibitors; liposarcomas showed modest responses to them [70,71]. However, the response rates were not high enough to obtain approval for a single-arm phase 2 trial, and further randomized clinical trials are necessary to confirm the clinical efficacies of CDK4 inhibitors.…”
Section: Investigating Molecular Targeted Therapies For Sts Patientsmentioning
confidence: 99%
“…Since many tumor cells merely arrest in response to Nutlin but resume proliferation once the drug is taken off, the clinical response might be transient at best. One way to get around this problem is to select tumors with a high frequency of Mdm2 amplifications, e. g. dedifferentiated liposarcomas [6, 7]. Another way to fortify the efficacy of Nutlin and related drugs would be to combine them with additional compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Because the basal level of p53 is low in HCT116 cells, an extremely low level of luciferase was driven by the basic promoter at the resting state, while enhanced luciferase activities would be detected in response to the increased p53 transcriptional activity in cells. All 181 candidates were evaluated using the high-throughput screening system following the indicated process in Figure 2B, together with MDM2 inhibitor SAR405838 [18] which induced a 3.6-fold increase in luciferase activities. To rule out the potential artificial positive results, compounds inducing changes more than 3.6-fold were believed as positive hits.…”
Section: Confirming Virtual Screening Results In Cellsmentioning
confidence: 99%